Adoption of Home-scale Biogas Digester Innovation in Suka Maju Farmer Group in Kaliboto Village of Mojogedang Sub District - Budiman, Anatta (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2019)
This research aimed to find out the farmers’ level of adoption to home-scale biogas digester as the form of cattle manure waste utilization in Suka Majufarmer group. This research employed descriptive qualitative approach, in which the data was collected using interview, observation, and focus group discussion (FGD) techniques. Data validation was carried out using source and method triangulations. The result of research showed that the process of adopting home-scale biogas digester innovation in Suka Maju farmer group has passed through awareness, interest, and evaluation stages. The members of group have not arrived at trial and adoption stage yet because they consider that the digester production cost (IDR 5,425,000) is substantial. The speed of home-scale biogas digester adoption process in Suka Maju farmer group is affected by the biogas digester’s innovative characteristic, particularly in triability aspect, and thedecision submitted to individual farmers.